Graft modification type magnetic MOF adsorbent, preparation method thereof and cannabinoid detection application
By combining graft-modified magnetic MOF adsorbent Fe3O4@poly (GMA/DVB-ZIF-8), combined with UHPLC-MS/MS technology, the problems of low recovery and low efficiency in cannabinoid detection in urine and saliva are solved, and the problem of low recovery rate and low efficiency in cannabinoid detection in urine and saliva is achieved. Four cannabinoid detections were efficient and fast, especially in saliva samples, which significantly improved detection efficiency and accuracy.
Patent Information
- Application Number
- CN202411293487.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The prior art has problems of low recovery rate, low efficiency and long-term consumption in the detection of cannabinoids in urine and saliva. Especially when saliva samples are small in size and low in drug content, more efficient means are needed for detection and analysis. .
The graft-modified magnetic MOF adsorbent Fe3O4@poly(GMA/DVB-ZIF-8) was used to modify the surface of 1-(3-aminopropyl)imidazole and Fe3O4@poly(GMA/DVB) microspheres, and zinc Salt and 2-methylimidazole self-assemble to form magnetic MOF material with ZIF-8 crystals grafted on the surface, combined with ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS/MS) and isotope internal calibration quantification method to achieve hemp Efficient and rapid detection of the stock.
Achieve efficient and rapid detection of four cannabinoids in urine or saliva. The recovery rate of urine samples exceeds 85%, and the recovery rate of saliva samples is between 89.5% and 106.3%, greatly shortening the pretreatment time and no complex nitrogen is required. The blowing steps are simple, fast and efficient.
Smart Images

Figure CN119175082A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of illegal drug detection, relates to a new adsorbent, and in particular to a grafted modified magnetic MOF adsorbent, a preparation method thereof, and cannabinoid detection application. Background Art
[0002] Drug abuse is a major concern in today's society. In order to effectively prevent drug abuse, it is necessary to accurately trace the source and crack down on drug crimes in order to curb the spread of drugs. Biological sample detection methods can accurately determine whether an individual has the behavior of taking drugs, and can obtain a more comprehensive and accurate picture of drug abuse, thereby helping relevant departments to formulate measures to achieve effective drug prevention and control. Analyzing the content of drugs and their metabolites in biological samples such as urine and saliva is the most direct means of diagnosing drug abuse. Therefore, it is very necessary to develop efficient and accurate analytical methods to detect drugs and their metabolism in biological samples.
[0003] The main components of cannabinoids are tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), etc. In judicial toxicology identification, commonly used biological samples include saliva, urine, hair and blood. At present, the main methods for enriching and extracting cannabinoids in biological matrices are liquid-liquid extraction and column-based solid-phase extraction. These two methods have the disadvantages of insufficient selectivity, low extraction efficiency, and complex and time-consuming operation. In particular, for samples such as saliva with small sample volume and low residual drug content, more efficient means are needed for detection and analysis.
[0004] Metal-organic framework materials (MOFs) are porous crystalline materials self-assembled from metal ions or metal ion clusters and organic ligands. Zeolite imidazolate framework-8 material (ZIF-8), as a classic MOF material, has a framework structure similar to zeolite, with Zn metal ions (M) connected by 2-methylimidazole (IM) bridges to form an IM-M-IM network. Due to its high stability, good dispersibility and excellent adsorption capacity for various analytes, it has been widely used in the adsorption and separation of various compounds. In addition, the structure of ZIF-8 has abundant imidazole groups and zinc metal ions. These chemical structures provide it with abundant π-π stacking and electrostatic interaction sites. At the same time, ZIF-8 also has strong hydrophobic properties. In view of the low recovery rate, low efficiency and long time consumption of the current pretreatment of cannabinoids in urine, as well as the problems faced by existing solid phase extraction adsorbents in the adsorption, extraction and detection of cannabinoids in saliva, the present invention introduces MOF material ZIF-8 by grafting modification to prepare a new magnetic MOF adsorbent material Fe3O4@poly(GMA / DVB-ZIF-8), combines it with ultra-high performance liquid chromatography-mass spectrometry (UHPLC-MS / MS), and establishes an isotope internal standard quantitative method for the detection of four cannabinoids, which can achieve efficient and rapid quantitative detection of cannabinoids in urine or saliva. Summary of the invention
[0005] The purpose of the present invention is to provide a graft-modified magnetic MOF adsorbent to address the deficiencies of the prior art, which can be used to quickly extract cannabinoids from urine or saliva. The present invention also provides a method for preparing the graft-modified magnetic MOF adsorbent and its application in extracting cannabinoids from urine or saliva.
[0006] The technical solution adopted by the present invention to solve its technical problem is:
[0007] A grafted modified magnetic MOF adsorbent is disclosed. The adsorbent utilizes the amine group of 1-(3-aminopropyl)imidazole to undergo a ring-opening reaction with epoxy to modify the imidazole functional group on the surface of Fe3O4@poly(GMA / DVB) microspheres. The amino imidazole on the surface of the microspheres undergoes a self-assembly reaction with zinc salt and 2-methylimidazole on the surface of the microspheres to obtain a magnetic MOF material Fe3O4@poly(GMA / DVB-ZIF-8) with ZIF-8 crystals grafted on the surface.
[0008] The preparation method thereof comprises the following steps:
[0009] Fe3O4@poly(GMA / DVB) microspheres were dispersed in a mixed solution of acetonitrile and water, 1-(3-aminopropyl)imidazole was added and ultrasonically homogenized, then the solution was transferred to a reactor and reacted at 80-100°C. After the reaction was completed, the reaction product was repeatedly washed with ultrapure water and ethanol by external magnetic adsorption to remove unreacted raw materials and impurities. The obtained reaction product was then placed in a three-necked flask equipped with a mechanical stirrer, methanol solution was added, and ZnCl2 and 2-methylimidazole were added at the same time, and the reaction was stirred. After the reaction was completed, the reaction product was alternately washed with ethanol and deionized water by external magnetic adsorption until the top of the solution was clear and free of suspended matter. The reaction product was taken out and dried to obtain a grafted modified magnetic MOF adsorbent Fe3O4@poly(GMA / DVB-ZIF-8).
[0010] In the above technical scheme, further, the Fe3O4@poly(GMA / DVB) microspheres are prepared by uniformly mixing oleic acid-modified Fe3O4 microsphere material OA-Fe3O4, glycidyl methacrylate (GMA), divinylbenzene (DVB) and porogen cyclohexane to obtain solution A, dissolving polyvinyl alcohol 1788 and sodium chloride in water and mixing them uniformly to obtain solution B, mixing solution A and solution B, ultrasonically crushing them in an ice bath, adding an initiator, and conducting a condensation reflux reaction under nitrogen protection to obtain the obtained solution. Wherein, preferably, the dosage ratio of OA-Fe3O4, GMA, DVB and cyclohexane in solution A can be generally 0.5g: (1.5-2.5) mL: (0.5-1.5) mL: (0.5-1.5) mL, the mass ratio of polyvinyl alcohol 1788 and sodium chloride in solution B is generally 1:5, and the volume ratio of solution A to solution B is generally (2.5-5.5): 150; the temperature of the condensation reflux reaction is 70°C, the stirring rate is 150r / min, and the reaction time is 6-12h. The oleic acid-modified Fe3O4 microsphere material OA-Fe3O4 can be obtained by dissolving FeCl3·6H2O in ethylene glycol, adding sodium acetate and polyethylene glycol 4000, heating to dissolve, transferring the obtained mixture to a reactor, heating to react; after the reaction is completed, putting it into oleic acid, heating and stirring to react.
[0011] Furthermore, the mass ratio of the Fe3O4@poly(GMA / DVB) microspheres to 1-(3-aminopropyl)imidazole is 1:(3-5).
[0012] Furthermore, the mixed solution is a solution of acetonitrile and water in a volume ratio of 1:1.
[0013] Furthermore, the mass ratio of ZnCl2 and 2-methylimidazole is 0.85:(1.1-1.7).
[0014] The application of the grafted modified magnetic MOF adsorbent in the detection of cannabinoids is to first use the adsorbent to separate and extract cannabinoids in urine or saliva, and then combine ultra-high performance liquid chromatography-mass spectrometry UHPLC-MS / MS analysis and isotope internal standard curve method to achieve quantitative analysis of cannabinoids, wherein the cannabinoids are tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), and tetrahydrocannabinolic acid (THC-COOH).
[0015] Among them, the method for separating and extracting cannabinoids includes the following: pre-treating the urine or saliva sample first, then mixing it with the activated adsorbent for extraction, after extraction, vortex washing the adsorbent with a washing solution, and then eluting the adsorbent with an eluent, and after the elution is completed, adjusting the pH of the obtained solution and filtering it for UHPLC-MS / MS analysis.
[0016] The adsorbent can be activated using methanol and ultrapure water sequentially;
[0017] The urine is pretreated as follows: the pH value of the urine sample is adjusted to 13 with sodium hydroxide solution, and the sample is placed in a water bath for hydrolysis reaction. After the hydrolysis is completed, the sample volume of 1 mL is diluted to 4 mL with ultrapure water, and the pH value of the sample is adjusted to 9-11 with hydrochloric acid solution; the corresponding washing solution is 5% MeOH / H2O, 10% MeOH / H2O, ACN, or MeOH, and the eluent is 0.5%, 1%, 3%, 5%, or 7% NH3·H2O / MeOH.
[0018] The saliva was pretreated as follows: 0.5 mL of saliva sample was taken, diluted to 4 mL with ultrapure water, and then the pH value was adjusted to 9-11 with sodium hydroxide solution; the corresponding washing solution was 10% MeOH / H2O, and the eluent was 5% NH3·H2O / MeOH.
[0019] The percentage indicates the volume concentration of the component before the slash in the component after it.
[0020] The beneficial effects of the present invention are:
[0021] The grafted modified magnetic MOF adsorbent Fe3O4@poly(GMA / DVB-ZIF-8) provided by the present invention has a simple preparation method, low cost and convenient use. It is applied to the detection of cannabinoids in urine or saliva, and can quickly extract four main cannabinoids from urine or saliva: tetrahydrocannabinol, cannabidiol, cannabinol and tetrahydrocannabinic acid, showing excellent extraction performance. The recovery rate of the four cannabinoids in urine samples under the optimal extraction conditions is more than 85%, and the recovery rate of the four cannabinoids in saliva samples is 89.5%-106.3%, with high recovery rate. The adsorption process of the four cannabinoids by Fe3O4@poly(GMA / DVB-ZIF-8) is completed by the synergy of hydrophobic effect, π-π stacking effect, electrostatic effect and Zn-O chelation. Compared with other pretreatment technologies, the magnetic solid phase extraction-ultra-high performance liquid chromatography-mass spectrometry (MSPE-UHPLC-MS / MS) method based on Fe3O4@poly(GMA / DVB-ZIF-8) can directly complete sample pretreatment for sample analysis without complicated steps such as nitrogen blowing, greatly shortening the pretreatment time. Especially for the detection of cannabinoids in saliva, the chance of sample adulteration can be reduced through non-invasive, simple and observable sample collection methods, and magnetic solid phase extraction can be directly performed without the hydrolysis treatment step, which is faster and more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM micrograph of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 1.
[0023] Figure 2 This is the EDS graph of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 1.
[0024] Figure 3 This is the infrared spectrum of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 1.
[0025] Figure 4 This is the nitrogen adsorption isotherm of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 1.
[0026] Figure 5 This is the energy spectrum scanning analysis diagram of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 1.
[0027] Figure 6 This is the effect of different elution solvents on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 2.
[0028] Figure 7This is the effect of different ammonia concentrations as elution solvent on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 2.
[0029] Figure 8 This is the effect of different washing solvents on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 2.
[0030] Fig. 9 This is the full XPS spectrum of the Fe3O4@poly(GMA / DVB-ZIF-8) sample in Example 5 before and after adsorption.
[0031] Fig.10 The XPS spectra of the Fe3O4@poly(GMA / DVB-ZIF-8) sample before and after adsorption of four cannabinoids in Example 5. (a) XPS C1s spectrum before adsorption, (b) XPS C1s spectrum after adsorption, (c) XPS N1s spectrum before adsorption, (d) XPS N1s spectrum after adsorption, (e) XPS Zn 2p spectrum before adsorption, and (f) XPS Zn 2p spectrum after adsorption.
[0032] Fig.11 This is the effect of different pH values on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 5.
[0033] Fig.12 This is the effect of different adsorption extraction times on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 5.
[0034] Fig.13 This is the effect of different surfactant concentrations on the extraction recovery rate in the magnetic solid phase extraction procedure in Example 5.
[0035] Table 1 shows the corresponding parameters of the internal standard quantitative method in Example 3.
[0036] Table 2 shows the spiked recovery and precision results of the method in Example 3 using urine matrix.
[0037] Table 3 shows the measured concentration of THC-COOH in the actual urine samples in Example 4.
[0038] Table 4 is the actual urine sample 10 spike recovery experiment in Example 4
[0039] Table 5 is a comparison of the detection concentration of THC-COOH in five actual urine samples by the magnetic solid phase extraction (MSPE) method of the present invention in Example 4 and the standard liquid-liquid extraction (LLE) method.
[0040] Table 6 shows the spike recovery and precision results of the method in Example 6 using saliva matrix.
[0041] Table 7 shows the spiked recoveries of the simulated positive saliva samples in Example 6. DETAILED DESCRIPTION
[0042] The technical solution of the present invention is further described in detail below through specific embodiments. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any form of modification and / or change made to the present invention will fall within the protection scope of the present invention.
[0043] Example 1
[0044] 1) Dissolve FeCl3·6H2O in ethylene glycol, add sodium acetate and polyethylene glycol 4000, heat to dissolve, transfer the obtained mixture to a reactor, and heat to react; after the reaction is completed, put the obtained Fe3O4 material into oleic acid, heat and stir to react, and then wash it repeatedly with water and ethanol for several times to obtain OA-Fe3O4;
[0045] 2) Take 0.5g of OA-Fe3O4, 2mL of glycidyl methacrylate (GMA), 1mL of divinylbenzene (DVB) and 1mL of porogen cyclohexane to prepare mixed solution A, and ultrasonically homogenize. Then take 0.3g of polyvinyl alcohol 1788 and 1.5g of sodium chloride and dissolve them in 150mL of aqueous solution to prepare solution B, and ultrasonically dissolve them. After solution B is completely mixed, solution A and solution B are mixed and placed in an ultrasonic cell crusher, and ultrasonically crushed under ice bath conditions (ultrasonic power 200W). When there is no obvious oil layer on the surface of the solution and it is in a uniform emulsion state, stop ultrasonication. Transfer the ultrasonic mixed solution to a three-necked flask equipped with a mechanical stirrer. Before the reaction is heated up, nitrogen is introduced for 30 minutes to remove the air in the reaction environment. After the air is removed, 0.08g of potassium persulfate (K2S2O8) is added to the reaction solution as an initiator. Then the reaction temperature is set to 70°C for condensation reflux reaction. The stirring rate is 150r / min, and nitrogen is continuously introduced during the reaction. After 8 hours of reaction, the obtained product Fe3O4@poly(GMA / DVB) magnetic microspheres are alternately washed several times with ethanol and deionized water by external magnet adsorption until the solution is clear and free of suspended matter. Finally, the cleaned Fe3O4@poly(GMA / DVB) is dispersed in an ethanol solvent and stored for later use;
[0046] 3) Take 0.5g of Fe3O4@poly(GMA / DVB) microspheres and disperse them in a mixed solution of acetonitrile and water (V / V, 1:1), then add 2.0g of 1-(3-aminopropyl)imidazole and ultrasonically homogenize, transfer the solution to a reactor, and react in an oven for 14h at a reaction temperature of 90°C. After the reaction is completed, the reaction product is repeatedly washed with ultrapure water and ethanol by external magnetic adsorption to remove unreacted raw materials and impurities, and the washed material is stored in a mixed solution of ethanol and water for later use;
[0047] 4) Take the reaction product from the previous step and wash it with methanol several times to remove water and other organic solvents on the material. Place the cleaned material in a three-necked flask equipped with a mechanical stirrer, add 60 mL of methanol solution, and add 0.85 g of ZnCl2 and 1.5 g of 2-methylimidazole at the same time. Stir the reaction at 40°C, the stirring rate is 200 r / min, and the reaction time is 48 hours. After the reaction is completed, the reaction product is alternately washed several times with ethanol and deionized water by external magnet adsorption until the solution is clear and there is no suspended matter. Subsequently, the material is placed in a vacuum drying oven at 60°C and dried for 14 hours before taking out. Finally, the magnetic MOF material Fe3O4@poly(GMA / DVB-ZIF-8) is obtained. Its SEM micrograph is shown as follows Figure 1 As shown, the EDS diagram is Figure 2 As shown, the infrared spectrum is Figure 3 The nitrogen adsorption isotherm is shown in Figure 4 As shown, the energy spectrum scanning analysis diagram is as follows Figure 5 shown.
[0048] Example 2
[0049] 1) Accurately weigh 5 mg of magnetic solid phase extraction adsorbent Fe3O4@poly (GMA / DVB-ZIF-8), and use 3 mL of methanol and ultrapure water to activate the adsorbent. After the urine sample is thawed at room temperature, sodium hydroxide solution is added to the thawed urine sample, the pH value of the solution is adjusted to 13, and then the solution is placed in a water bath for hydrolysis reaction. The hydrolysis temperature is 60 ° C and the duration is 20 min. After the hydrolysis is completed, take 1 mL of the urine sample and transfer it to a 10 mL glass test tube, then dilute the urine volume to 4 mL with ultrapure water, and adjust the pH value of the sample to 11 with hydrochloric acid solution. After the sample treatment is completed, add 5 mg of magnetic solid phase extraction adsorbent Fe3O4@poly (GMA / DVB-ZIF-8) for dispersed extraction, oscillate and extract the above dispersed solution for about 5 minutes, and separate the adsorbent from the urine sample by an external magnetic field.
[0050] 2) Use 500 μL of detergent (5% MeOH / H2O, 10% MeOH / H2O, ACN, or MeOH) to vortex wash the magnetic solid phase extraction adsorbent for 30 seconds. After washing, the analyte is eluted by adding 200 μL of eluent (5% NH3·H2O / MeOH, 5% HCOOH / MeOH, or 5% TFA / MeOH, or different concentrations of NH3·H2O / MeOH) to the glass test tube and eluting by vortexing for 30 seconds. After elution, the adsorbent and the solution are separated to both sides of the glass test tube by an external magnetic field again, and the elution solution is taken out from the side of the glass tube with a pipette, and 5 μL of formic acid solution is added to the elution solution to adjust the pH. Then, a 0.22 μm pore size aqueous needle filter membrane is used for filtration, and finally the filtered solution is transferred to a liquid injection vial for UHPLC-MS / MS analysis.
[0051] The effects of different detergents and eluents on the extraction recovery were investigated. Figure 6 , 7 , 8. When 10% MeOH / H2O was used as the washing solvent and 5% NH3·H2O / MeOH was used as the elution solvent, the recovery rate of the four analytes was the best.
[0052] Example 3
[0053] 1) The isotope internal standard curve method was used for the qualitative and quantitative analysis of four cannabinoids in urine. The relevant validation parameters of the internal standard method are shown in Table 1, where the corresponding concentrations of the signal-to-noise ratio S / N=3 and S / N=10 were determined as the method detection limits (LODs) and quantification limits (LOQs) to evaluate the sensitivity of the method. The detection limits and quantification limits of the four cannabinoids were 0.017ng / mL and 0.05ng / mL, respectively. The relationship between the peak area and the analyte concentration obtained by UHPLC-MS / MS analysis was used to prepare the internal standard curves of the four cannabinoids. The linear ranges of THC, CBD, and CBN were 0.05-5ng / mL, and the linear range of THC-COOH was 0.05-25ng / mL.
[0054] 2) The accuracy of the method was investigated by conducting spike recovery experiments on urine matrix. Three concentration levels of low, medium and high within the linear range were selected for spike recovery experiments. As shown in Table 2, the spike recoveries of THC, CBD, CBN and THC-COOH in urine were 85.1-95.2%, 92.8-104.2%, 87.9-93.8% and 84.7-104.7%, respectively. The intra-day precision and inter-day precision of the urine matrix were less than 5.8% and 7.6%, respectively. The above results show that the established analytical method has a low detection limit, good accuracy and reproducibility, and meets the requirements of relevant standards. It can meet the detection of four cannabinoids THC, CBN, CBD and THC-COOH in urine samples.
[0055] Table 1
[0056]
[0057] Table 2
[0058]
[0059]
[0060] Example 4
[0061] 1) In order to further evaluate the applicability of Fe3O4@poly(GMA / DVB-ZIF-8) adsorbent and the effectiveness of the method, Fe3O4@poly(GMA / DVB-ZIF-8) was used as a pretreatment for magnetic solid phase extraction and combined with the established analytical method, it was applied to the urine of people who had smoked marijuana for detection and analysis. A total of 18 actual urine samples were tested, and the test results are shown in Table 3. THC-COOH was detected in all 18 samples, with a concentration range of 0.104-3.170 ng / L, while THC, CBD and CBN were not detected in any urine samples.
[0062] In the subsequent study, in order to further verify the accuracy of the method, one of the positive urine samples (sample 10) was selected for a spike recovery experiment. As shown in Table 4, it can be seen that the spike recovery of THC-COOH is between 89.1% and 97.8%, which shows that the method has good accuracy. Subsequently, the test results of the standard liquid-liquid extraction method (LLE) and the magnetic solid phase extraction method were compared, and the analysis results of five samples were selected for comparison. The results are shown in Table 5. There is no significant difference in the results detected by the two methods, and the relative difference is less than 6.0%. The above results show that the established method has good accuracy and practicality, and can be applied to the analysis and detection of 4 cannabinoids in urine samples.
[0063] Table 3
[0064]
[0065] Table 4
[0066]
[0067] Table 5
[0068]
[0069] Example 5
[0070] 1) Accurately weigh 5 mg of magnetic solid phase extraction adsorbent Fe3O4@poly (GMA / DVB-ZIF-8), and use 3 mL of methanol and ultrapure water to activate the adsorbent. Take 0.5 mL of saliva sample in a 10 mL glass test tube, dilute the saliva sample to 4 mL with ultrapure water, and adjust the pH value of the solution with sodium hydroxide. Add 5 mg of magnetic solid phase extraction adsorbent directly to the pH-adjusted saliva sample for adsorption extraction, and then use 500 μL of 10% MeOH / H2O washing solution to vortex wash the magnetic solid phase extraction adsorbent for 30 seconds.
[0071] 2) After washing, the analyte was eluted by adding 100 μL 5% NH3·H2O / MeOH to the glass test tube and eluting by vortexing for 30 seconds. After elution, the adsorbent and the solution were separated to both sides of the glass test tube by an external magnetic field again, and the elution solution was taken out from the side of the glass tube using a pipette, and 5 μL formic acid solution was added to the elution solution to adjust the pH. Then, the analyte was filtered using a 0.22 μm pore size aqueous needle filter membrane, and the filtered solution was transferred to a liquid injection vial for UHPLC-MS / MS analysis.
[0072] In this example, the effects of different solution pH values, adsorption extraction time, and surfactant concentration (surfactant added before solution extraction) on the extraction recovery rate were investigated. Fig.11 , 12 , as shown in Figure 13. Taking all factors into consideration, pH = 11, adsorption time 5min, and no addition of surfactant are the optimal sample extraction conditions. The dodecyl group in the structure of the surfactant (sodium dodecyl sulfate, SDS) has extremely strong hydrophobic properties, which will destroy the hydrophobic interaction between the cannabinoids and the adsorbent. At the same time, the alkalinity of the SDS aqueous solution will inhibit the ionization of the adsorbed imidazole group, thereby affecting the electrostatic interaction between the adsorbent and the cannabinoids. Therefore, when the surfactant concentration is 0, the extraction efficiency of the four cannabinoids is the highest. Under the optimal extraction conditions, the full XPS spectrum of the sample before and after adsorption is shown in Figure 13. Fig. 9As shown, the XPS spectra of the samples before and after adsorption of four cannabinoids are as follows Fig.10 shown.
[0073] Example 6
[0074] 1) The isotope internal standard curve method was used for the qualitative and quantitative analysis of four cannabinoids in saliva. The relevant validation parameters of the internal standard method are shown in Table 6, where the corresponding concentrations of the signal-to-noise ratio S / N=3 and S / N=10 were determined as the method detection limits (LODs) and quantification limits (LOQs) to evaluate the sensitivity of the method. The detection limits and quantification limits of the four cannabinoids were 0.017ng / mL and 0.05ng / mL, respectively. The relationship between the peak area and the analyte concentration obtained by UHPLC-MS / MS analysis was used to prepare the internal standard curves of the four cannabinoids. The linear ranges of THC, CBD, and CBN were 0.05-5ng / mL, and the linear range of THC-COOH was 0.05-25ng / mL.
[0075] 2) The saliva matrix was subjected to a spike recovery experiment to examine the accuracy of the method. Three concentration levels of low, medium and high within the linear range were selected for spike recovery experiments. As shown in Table 6, the spike recoveries of THC, CBD, CBN and THC-COOH in saliva were 87.7-92.9%, 96.0-106.5%, 92.9-104.4% and 91.7-99.3%, respectively. The intra-day precision and inter-day precision of the saliva matrix were less than 11.4% and 13.8%, respectively. This indicates that the established analytical method has a low detection limit, good accuracy and reproducibility, and meets the requirements of relevant standards. It can meet the detection of four cannabinoids, THC, CBN, CBD and THC-COOH, in saliva samples.
[0076] 3) The simulated positive samples were prepared by adding, and the content of the standard added was detected and analyzed, and then the simulated positive samples were subjected to spike recovery experiments to examine the accuracy and applicability of the method. The results are shown in Table 7. The spike recovery rates of the four cannabinoids were between 89.5% and 106.3%. The above results show that the established method has good accuracy and practicality, and can be applied to the analysis and detection of the four cannabinoids in saliva samples.
[0077] Table 6
[0078]
[0079] Table 7
[0080]
[0081] The above-described embodiment is only a preferred solution of the present invention and does not limit the present invention in any form. There are other variations and modifications without exceeding the technical solution described in the claims.
Claims
1. A grafted modified magnetic MOF adsorbent, characterized in that: The adsorbent utilizes the ring-opening reaction between the amine group of 1-(3-aminopropyl)imidazole and epoxy to modify the imidazole functional group on the surface of Fe3O4@poly(GMA / DVB) microspheres, and then the amino imidazole on the surface of the microspheres reacts with zinc salt and 2-methylimidazole to self-assemble on the surface of the microspheres to obtain the magnetic MOF material Fe3O4@poly(GMA / DVB-ZIF-8) with ZIF-8 crystals grafted on the surface.
2. The method for preparing the graft-modified magnetic MOF adsorbent according to claim 1, characterized in that: These include: Fe3O4@poly(GMA / DVB) microspheres were dispersed in a mixed solution of acetonitrile and water, 1-(3-aminopropyl)imidazole was added and ultrasonically homogenized, then the solution was transferred to a reactor and reacted at 80-100°C. After the reaction was completed, the reaction product was repeatedly washed with ultrapure water and ethanol by external magnetic adsorption to remove unreacted raw materials and impurities. The obtained reaction product was then placed in a three-necked flask equipped with a mechanical stirrer, methanol solution was added, and ZnCl2 and 2-methylimidazole were added at the same time, and the reaction was stirred. After the reaction was completed, the reaction product was alternately washed with ethanol and deionized water by external magnetic adsorption until the top of the solution was clear and free of suspended matter. The reaction product was taken out and dried to obtain a grafted modified magnetic MOF adsorbent Fe3O4@poly(GMA / DVB-ZIF-8).
3. The method for preparing the graft-modified magnetic MOF adsorbent according to claim 2, characterized in that: The Fe3O4@poly(GMA / DVB) microspheres are prepared by uniformly mixing oleic acid-modified Fe3O4 microsphere material OA-Fe3O4, glycidyl methacrylate (GMA), divinylbenzene (DVB) and porogen cyclohexane to obtain a solution A, dissolving polyvinyl alcohol 1788 and sodium chloride in water and mixing them uniformly to obtain a solution B, mixing the solution A and the solution B, performing ultrasonic crushing in an ice bath, adding an initiator, and performing a condensation reflux reaction under nitrogen protection to obtain the obtained product.
4. The method for preparing the graft-modified magnetic MOF adsorbent according to claim 2, characterized in that: The mass ratio of the Fe3O4@poly(GMA / DVB) microspheres to 1-(3-aminopropyl)imidazole is 1:(3-5).
5. The method for preparing the graft-modified magnetic MOF adsorbent according to claim 2, characterized in that: The mixed solution is a solution of acetonitrile and water in a volume ratio of 1:
1.
6. The method for preparing the graft-modified magnetic MOF adsorbent according to claim 2, characterized in that: The mass ratio of ZnCl2 and 2-methylimidazole 0.85:(1.1-1.7)。 7. The use of the grafted modified magnetic MOF adsorbent in cannabinoid detection according to claim 1, characterized in that: The adsorbent is first used to separate and extract cannabinoids in urine or saliva, and then combined with ultra-high performance liquid chromatography-mass spectrometry UHPLC-MS / MS analysis and isotope internal standard curve method to achieve quantitative analysis of cannabinoids, wherein the cannabinoids are tetrahydrocannabinol (THC), cannabidiol (CBD), cannabinol (CBN), and tetrahydrocannabinolic acid (THC-COOH).
8. The use according to claim 7, characterized in that: The method for separating and extracting cannabinoids includes the following: pre-treating the urine or saliva sample, then mixing it with the activated adsorbent for extraction, vortex-washing the adsorbent with a washing solution after extraction, and then eluting the adsorbent with an eluent, and adjusting the pH of the resulting solution after elution and filtering it for UHPLC-MS / MS analysis.
9. The use according to claim 8, characterized in that: The urine is pretreated as follows: the pH value of the urine sample is adjusted to 13 with sodium hydroxide solution, and the sample is placed in a water bath for hydrolysis reaction. After the hydrolysis is completed, the sample volume of 1 mL is diluted to 4 mL with ultrapure water, and the pH value of the sample is adjusted to 9-11 with hydrochloric acid solution; the corresponding washing solution is 5% MeOH / H2O, 10% MeOH / H2O, ACN, or MeOH, and the eluent is 0.5%, 1%, 3%, 5%, or 7% NH3·H2O / MeOH.
10. The use according to claim 8, characterized in that: The saliva was pretreated as follows: 0.5 mL of saliva sample was taken, diluted to 4 mL with ultrapure water, and then the pH value was adjusted to 9-11 with sodium hydroxide solution; the corresponding washing solution was 10% MeOH / H2O, and the eluent was 5% NH3·H2O / MeOH.
Citation Information
Patent Citations
Preparation method and application of novel solid-phase extractant
CN107224968A
Fluorinated squaramide covalent organic framework material as well as preparation method and application thereof
CN116693786A
Preparation method of magnetic carboxyl chitosan microsphere and metal organic framework core-shell structure industrial catalyst
CN117299204A
Application of magnetic nano material in detection of synthetic cannabinoid drugs
CN118225928A
Cited By
High-porosity wet-process diaphragm and preparation method thereof
CN121238158A
